Upaya Peningkatan Prestasi Belajar Melalui Model Problem Based Learning (PBL) Berbantuan Media Pembelajaran Wordwall Siswa Sekolah Dasar - Farachdila, Restu; Irawan*, Dedy (Universitas Negeri Makassar, 2024)
This research is motivated by the low learning achievement of students in the Pancasila Education subject in grade V of SD Negeri 1 Karanggintung. The low learning achievement is caused by teachers not using learning models and media in the learning process. This research method used is Classroom Action Research (CAR) conducted in two cycles. The results show that the Problem-Based Learning (PBL) learning model assisted by wordwall learning media can enhance students' learning achievement in the Pancasila Education subject. Enhancement can be seen from the calculation of the percentage of students' learning achievement mastery which continues to increase in each cycle. In the first cycle, the percentage of students' learning achievement mastery is 51.79% with a fairly good criterion. In the second cycle, the percentage of students learning achievement mastery increased to 83.93% with a very good criterion. Thus, it can be concluded that the use of the Problem-Based Learning (PBL) learning model assisted by wordwall learning media can enhance students' learning achievement in the Pancasila Education subject in grade V of SD Negeri 1 Karanggintung.